Long‐term analysis of children with metastatic neuroblastoma treated in the ENSG5 randomised clinical trial. Issue 4 (5th December 2018) - Moreno, Lucas; Vaidya, Sucheta J.; Schrey, Dominik; Pinkerton, C. Ross; Lewis, Ian J.; Kearns, Pamela R.; Machin, David; Pearson, Andrew D. J.
Abstract: Background: The European Neuroblastoma Study Group 5 (ENSG5) trial showed that time‐intensive "rapid" induction chemotherapy (COJEC) was superior to "standard" 3‐weekly chemotherapy for children with high‐risk metastatic neuroblastoma. Long‐term outcomes of the ENSG5 trial were analysed. Procedure: Patients with metastatic neuroblastoma aged ≥12 months were randomly assigned to "standard" or "rapid" induction, receiving the same chemotherapy drugs and doses. Event‐free survival (EFS) and overall survival (OS) were analysed and prognostic factors evaluated. Amongst patients surviving >5 years, a population of children with persistent metastatic disease after the end of treatment was identified and described. Results: Ten‐year EFS was 18.2% (95% confidence interval: 12.2–25.2) for the "standard" arm and 26.8% (19.5–34.7) for the "rapid" arm (hazard ratio [HR] 0.85, P  = 0.28). Ten‐year OS for the "standard" arm was 19.7% (13.4–26.8) and 28.3% (20.8‐36.2) for the "rapid arm" (HR 0.83, P  = 0.19). There was a trend for worse EFS and OS for patients having MYCN amplification (HR 1.37 and 1.40, respectively) and those with partial and mixed response to induction (HR 1.69 and 1.75 for EFS and 1.66 and 2.00 for OS, respectively). Among 69 patients who survived >5 years, six had persistent metastatic disease after the end of treatment. Conclusion: The benefit of the "rapid" induction regimen seems to be maintained in the long term, although the small number of survivors could justify the lack of statistical significance. MYCN amplification and poor metastatic response to induction could be associated with worse outcomes. A small group of patients with persistent metastatic disease that survived long term has been described.